Imagination Therapy through Art and Technology: A Collaborative Mental Health Intervention - Aditya Wahyu Ramadhan; Eko Supriyanto; Handriyotopo Handriyotopo (Electronic Journal of Education, Social Economics and Technology, 2025)
This research explores imagination therapy as a creative method aimed at providing visual therapy for ten schizophrenic clients, referred to as "chosen people." Utilizing the concept of hyperreality, the therapy seeks to reactivate cognitive abilities and minimize delusions and hallucinations. Hyperreality is constructed from imagined data, drawing from clients' personal documents, archives, and daily life elements, such as songs, objects, and routines. Imagination therapy integrates clients' unrealized stories, desires, and imaginations with hyperrealistic visuals through collaborative sessions. The process involves repeated evaluations to refine visuals based on client preferences and feedback, ultimately culminating in the creation of a visual lab. The therapy’s effectiveness is assessed using the PANSS (Positive and Negative Syndrome Scale), measuring symptom changes over time. The findings indicate that imagination therapy not only fosters confidence in clients’ ability to process their expectations but also helps reactivate cognitive functions and empower desires. The concept of hyperreality proves essential in enhancing self-confidence and enabling clients to realize their deepest desires, contributing to their overall mental health recovery. This study highlights the potential of using artistic and technological methods in schizophrenia treatment.